Reference Architecture of Intelligent System - Teresius, V. (Elektronika ir Elektrotechnika, 2005)
Intelligent agents continuously perform following functions: perception of dynamic conditions in the environment; action to affect conditions in the environment; and interpreting perceptions, solve problems. The architecture of intelligent control system, general components of intelligent system and interconnections between them is introduced in this article. Any intelligent control system consist of two parts: internal (computational) and external – interface between the real world and application. The internal part can be decomposed into four modules: sensory processing, world modeling, behaviour generation and value judgement. Input to internal part of intelligent system are realized by sensors, and output – by actuators. Intelligent systems represent increment in behavioral requirements compared to typical control systems. Ill. 3, bibl. 8 (in English; summaries in Lithuanian, English and Russian).